Integrative transcriptomic analysis reveals the molecular responses of tobacco to magnesium deficiency - Liang, Tingmin; Lin, Jinbin; Wu, Shengxin; Ye, Rongrong; Qu, Mengyu; Xie, Rongrong; Lin, Yingfeng; Gao, Jingjuan; Wang, Yuemin; Ke, Yuqin; Li, Chunying; Guo, Jinping; et al. (Frontiers in Plant Science, 2024)
Magnesium (Mg) is a crucial macronutrient for plants. Understanding the molecular responses of plants to different levels of Mg supply is important for improving cultivation practices and breeding new varieties with efficient Mg utilization. In this study, we conducted a comprehensive transcriptome analysis on tobacco (Nicotiana tabacum L.) seedling leaves to investigate changes in gene expression in response to different levels of Mg supply, including Mg-deficient, 1/4-normal Mg, normal Mg, and 4×-normal Mg, with a particular focus on Mg deficiency at 5, 15 and 25 days after treatment (DAT), respectively. A total of 11,267 differentially expressed genes (DEGs) were identified in the Mg-deficient, 1/4-normal Mg, and/or 4×-normal Mg seedlings compared to the normal Mg seedlings. The global gene expression profiles revealed potential mechanisms involved in the response to Mg deficiency in tobacco leaves, including down-regulation of genes-two DEGs encoding mitochondria-localized NtMGT7 and NtMGT9 homologs, and one DEG encoding a tonoplast-localized NtMHX1 homolog-associated with Mg trafficking from the cytosol to mitochondria and vacuoles, decreased expression of genes linked to photosynthesis and carbon fixation at later stages, and up-regulation of genes related to antioxidant defenses, such as NtPODs, NtPrxs, and NtGSTs. Our findings provide new insights into the molecular mechanisms underlying how tobacco responds to Mg deficiency.